2018
DOI: 10.1134/s2079970518010112
|View full text |Cite
|
Sign up to set email alerts
|

Population Dynamics in Towns of Leningrad Oblast: Effects of the Crisis of 2014–2016

Abstract: Socioeconomic development in cities and towns is a complex and multifactor phenomenon with various dimensions and evaluation criteria. One of the simplest and most available indicators of a situation in the economic and social sphere is population size dynamics. Using the towns of Leningrad oblast as an example, we analyzed how the 2014-2016 crisis events in the Russian economy affected the population dynamics. Starting from the 1980s, the towns of Leningrad oblast have been developing multidirectionally-in so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
2
0
0
Order By: Relevance
“…The new educational institutions are of different levels from pre-primary unit to tertiary which have been established to cater to the growing education demand of the increased population. The above results harmonize to the findings by Zhitin and Shendrik, (2018) in Russia and Mlambo, (2018) in South Africa.…”
Section: Effects Of Population Dynamics In the Study Area 331 Positiv...supporting
confidence: 91%
See 1 more Smart Citation
“…The new educational institutions are of different levels from pre-primary unit to tertiary which have been established to cater to the growing education demand of the increased population. The above results harmonize to the findings by Zhitin and Shendrik, (2018) in Russia and Mlambo, (2018) in South Africa.…”
Section: Effects Of Population Dynamics In the Study Area 331 Positiv...supporting
confidence: 91%
“…Respondents further reported that investment in services and business has created employment opportunities particularly in the transport sector where many youths are currently self-Iringa Municipality, Tanzania 55 employed in transport services particularly in motor vehicles (Bajaj and Bodaboda) which have improved their livelihood through income earning. These results are supported by Zhitin & Shendrik (2018) who reports that changes in population trends in Russia due to in-migration culminated to amid rapid changes in the rate of economic increase.…”
Section: Effects Of Population Dynamics In the Study Area 331 Positiv...supporting
confidence: 67%